Ultrasound-guided sclerotherapy with 76% meglumine diatrizoate for bilateral chylothorax after thyroid cancer surgery: a case report - Luo, Qinhui; Peng, You; Lao, Liangling; Hu, Xiaolei; Xie, Jianlong; Luo, Jianming; Luo, Hongjie; Lin, Liyao (Frontiers in Oncology, 2026)
Bilateral chylothorax following thyroid cancer surgery is exceedingly rare, and management becomes more challenging when one side presents as high-output (>1,000 mL/day). Conservative treatments often yield limited success. We report a case of recurrent papillary thyroid carcinoma in which bilateral chylothorax was diagnosed on postoperative day (POD) 5 by chest radiography and qualitative chyle tests, with right-sided drainage exceeding 1,000 mL/day. After 19 days of ineffective conservative therapy, 76% meglumine diatrizoate was percutaneously injected into the lymphatic leak site under ultrasound guidance, followed by external compression. The drainage volume decreased significantly and fully resolved within 10 days, without systemic adverse effects. To our knowledge, this is the first report of successful treatment of bilateral chylothorax after thyroidectomy using this approach. The findings suggest that local sclerotherapy with meglumine diatrizoate offers a minimally invasive, safe, and technically simple alternative, particularly for patients who fail conservative therapy but are not suitable surgical candidates.